(untitled) (Zaranie Śląskie, 2025)
This article offers a critical analysis of the dominant narrative concerning the area on which the Voivodeship Park of Culture and Recreation (WPKiW) – today’s Silesian Park – was established. The author challenges the entrenched image, perpetuated in literature, media, and institutional picture of the future park, as a degraded, post-industrial wasteland. On the basis of archival sources, press and photographs, the study demonstrates that the majority of the land designated for the WPKiW had an agricultural character. Particular attention is given to a 1950 terrain survey, which shows that most of the area intended for the park consisted of medium-quality arable land. Supplementary evidence includes press reports and photographs depicting an organized agricultural landscape. The narrative of total land degradation before the park’s creation finds no confirmation in the sources. On the contrary, the available materials point to a diverse, predominantly agricultural environment, enabling a revision of the founding myth of Silesian Park. The author argues that the vision of a „lunar landscape” was a propagandistic construct that began to dominate media discourse only from 1954 onwards, in connection with the regional program for the reclamation of spoil heaps and wastelands.